Partnership Model of PT. Pabrik Gula Candi Baru Sidoarjo with Sugarcane Farmers (TRK) - Fredella, Femy Atha; Soedarto, Teguh; Atasa, Dita (Forum Agribisnis, 2025)
Sugar factories operating in Sidoarjo Regency began to decline, this was due to land function experts to machine parts damage. PT. Pabrik Gula Candi Baru Sidoarjo is a sugar-based agroindustry that has remained operational near the center of Sidoarjo Regency. The company's land sugarcane harvest in the procurement of sugarcane raw materials has not met the grinding target. So it needs a fixed partner to meet the grinding target and so that the company continues to operate. The research was conducted to analyze 1) the partnership pattern of PT. Pabrik Gula Candi Baru Sidoarjo with sugar cane farmers partnership (TRK), 2) The motivational level of partnership sugarcane farmers (TRK) maintains cooperative relationships with companies and 3) analyzes farmers' income earned once the planting season. Research was conducted in May–November 2024 in Candi District, Sidoarjo Regency. The population of the study respondents was 363 partnership sugarcane farmers (TRK) through a Slovine calculation and a 15% error rate, a study sample of 40 respondents obtained. Research uses descriptive analysis to determine partnership patterns, motivational levels using the likert scale and cost of farming, receiving, and income of farmers with income analysis. The research results state that the partnership pattern of PT. Pabrik Gula Candi Baru Sidoarjo with sugarcane farmers partnership (TRK) is in the form of a plasma core. As well as the level of motivation for partnership sugarcane farmers (TRK) in partnership with companies is classified as a strong category with an 80% percentage that farmers expect consistent profits. The sugarcane cultivation business of partnership sugarcane farmers (TRK) costs Rp32. 093.349/ha, revenue of Rp52.879.420/ha and revenue of Rp20.786.071/ha. Thus, the conclusion of this study was that partnerships could convince farmers of the potential of the agricultural business and maintain sugarcane farming businesses by providing proper income.